Risk and health effect of boric acid - Ang, Swi See; Salleh, Abu Bakar; Abu Bakar, Fatimah; Yusof, Nor Azah; Abdulamir, Ahmed Sahib; Lee, Yook Heng (Science Publications, 2010)
Problem statement: Boric acid is a pesticide usually used to kill mites, fungi, plants and insect including fleas, termites, cockroaches and wood decay fungi. Besides, it was also used in many fields such as food preservative, in newborn baby’s nurseries and antiseptic. Many reports indicated that boric acid poisoning occurred due to the misuse of household product and illegal use of boric acid in food product. In this study, the concern issue was the usage of boric acid that may lead to boric acid poisoning. Approach: This review had shown some information for boric acid such as its usage, the existent method for detection of boric acid in food. Besides, this review also discussed about the toxicology and pharmacokinetic of boric acid and the health impact of boric acid on human and animal. Result: Previous studies showed that food products such as yellow noodles contain boric acid. The boric acid level in most foods was different among the factory and the production period. It is due to the lack of standard measurement during the processing. Conclusion: Since boric acid was harmful to human health and may cause poisoning, hence, the control and the awareness of the usage of boric acid especially in food should be increased. There are numerous methods available for quantification of boric acid such as mannitol titration technique, colorimetric method. Accordingly, the analysis of boric acid is essential.